Analysis of rigid pavements on ground improved by geosynthetics and stone columns. Issue 4 (21st September 2018) - Murakonda, Pavani; Maheshwari, Priti
Abstract : Stone columns and geosynthetics have been widely used as effective stabilisation techniques to improve the load–settlement response of foundations. In view of this, an analysis of rigid pavements resting on geosynthetic-reinforced granular bed–stone column improved subgrade soil has been carried out. A detailed idealisation of the problem has been done using elements of Kelvin–Voigt body, Pasternak shear layer and Winkler springs, respectively, to simulate the behaviour of subgrade soil, granular fill and stone columns. A non-linear constitutive relationship for these elements has been considered. Governing differential equations for the soil–pavement system have been developed by modelling the geosynthetic as a rough elastic membrane and the pavement as a thin plate. These equations have been written in their finite-difference form and solved using the lower–upper (LU) decomposition method with the help of appropriate boundary conditions. A detailed parametric study to depict the influence of various factors affecting the pavement behaviour has been carried out. Quantitative evaluation of this influence has been done to enable the deflection and bending moment in the pavement and the tension mobilised in the geosynthetic layer to be obtained.